2011
DOI: 10.1016/j.pmrj.2011.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Changes in Spinal Height and Pain After Aquatic Vertical Traction in Patients With Persistent Low Back Symptoms: A Crossover Clinical Trial

Abstract: Although both the aquatic and land interventions produced significant increases in overall spinal height, the aquatic intervention produced greater pain relief and centralization response in subjects with low back pain and signs of nerve root compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Kim et al found the a tilt degree of 60 resulted in improve levels of pain, spine flexibility and trunk extensors strength compared to tilt degrees of 30 or 0 (supine position) [ 13 ]. Further, Simmerman et al found that aquatic traction resulted in significant pain reduction and centralization of symptoms compared to land-based exercises in patients with chronic LBP associated with nerve root compression symptoms [ 14 ]. Finally, Diab and Moustafa found that traction in combination with stretching and infrared radiation resulted in significant improvement of pain and disability levels compared to stretching and infrared in patients with chronic LBP at 6 months [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al found the a tilt degree of 60 resulted in improve levels of pain, spine flexibility and trunk extensors strength compared to tilt degrees of 30 or 0 (supine position) [ 13 ]. Further, Simmerman et al found that aquatic traction resulted in significant pain reduction and centralization of symptoms compared to land-based exercises in patients with chronic LBP associated with nerve root compression symptoms [ 14 ]. Finally, Diab and Moustafa found that traction in combination with stretching and infrared radiation resulted in significant improvement of pain and disability levels compared to stretching and infrared in patients with chronic LBP at 6 months [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, if we studied the overall impact of swimming, it would most probably be evident that while swimming has beneficial effects on muscles and the spine, in general, because muscles actively engaged in swimming contract, the stretching in the spine is less effective than in an inactive, relaxed position during hydrotraction suspension. Simmerman et al showed in a crossover trial with 30 participants that the aquatic vertical traction results in short-term improvements of the low back pain (Simmerman et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that land-based therapeutic exercise in chronic LBP with nerve compression symptoms are not so effective in pain reduction if the patient first receives aquatic traction therapy (Simmerman et al 2011 ) .…”
Section: Introductionmentioning
confidence: 99%
“… 35 The divergence between clinical practice and recommendations from systematic reviews may be related to the empirical evidence that supports the benefits of lumbar traction. 35 37 These studies indicated the potential efficacy of NSSD in patients with LBP.…”
Section: Introductionmentioning
confidence: 90%